Lymphoid-specific helicase inhibits cervical cancer cells ferroptosis by promoting Nrf2 expression - Tie,Weiwei; Ge,Fenfen (PeerJ, 2023)
Background Cervical cancer is a major cause of morbidity and mortality in women worldwide. The underlying mechanisms of its progression are not well understood. In this study, we investigated the role of lymphoid-specific helicase (HELLS) in cervical cancer. Methods We measured HELLS expression in cervical cancer and assessed its function using gain- and loss-of-function experiments. Cell viability was measured using the Cell Counting Kit-8 (CCK8 ) assay, and cell proliferation was analyzed using colony formation and EdU assays. Results We found that HELLS was significantly increased in cervical cancer and that its overexpression promoted cell viability (P < 0.01) and colony formation (P < 0.001). In contrast, si-HELLS suppressed these effects. Moreover, HELLS overexpression inhibited cell death induced by the ferroptosis inducer erastin (P < 0.01). Mechanistically, we found that HELLS promoted cervical cancer proliferation by regulating nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated ferroptosis. Conclusion Our data suggest that HELLS promotes cervical cancer proliferation by inhibiting Nrf2 expression. Therefore, HELLS knockdown may be an effective treatment for cervical cancer.
Keywords: Cervical cancer; Ferroptosis; Lymphoid-specific helicase; Nuclear factor erythroid 2-related factor 2